2022
DOI: 10.1007/s11440-022-01689-0
|View full text |Cite
|
Sign up to set email alerts
|

BCV bentonite hydromechanical behaviour and modelling

Abstract: It is assumed that clay materials such as bentonites will be used as the buffer and backfill of high-level radioactive waste disposal. Due to the very long timescale, the design can be based only on mathematical models that have been thoroughly validated via the use of high-quality laboratory data. The presentation of an extensive laboratory dataset, accompanied by the validation of a bentonite constitutive model, comprises the main topic of this paper. The objectives of the laboratory research were to determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 10 publications
(11 reference statements)
0
6
0
Order By: Relevance
“…In the present work, the coupled hypoplastic model for unsaturated fine-grained soils developed by Wong and Mašín [7] was further extended to include a smoothed hysteretic water retention curve formulation proposed by Svoboda et al [9] The model shows better predictions of the hydraulic soil behaviour, because it is able to capture the non-linear dependency of suction on the degree of saturation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present work, the coupled hypoplastic model for unsaturated fine-grained soils developed by Wong and Mašín [7] was further extended to include a smoothed hysteretic water retention curve formulation proposed by Svoboda et al [9] The model shows better predictions of the hydraulic soil behaviour, because it is able to capture the non-linear dependency of suction on the degree of saturation.…”
Section: Discussionmentioning
confidence: 99%
“…The reference model adopted a hysteretic bi-linear water retention curve following the formulation by Brooks and Corey [8], see Fig 1 . However, experimental evidence has indicated that the dependency of suction on the degree of saturation is non-linear [10]. For this reason, a smoothed WRC proposed by Svoboda et al [9] was incorporated into the original model. The smoothed formulation also improves the numerical performance of the model, avoiding abruptly changes at the intersection of the main wetting/drying curves with the scanning curve and at the air entry/expulsion suction value due to the derivates of .…”
Section: Modified Hysteretic Water Retention Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The cation exchange capacity reaches 60.9 meq/100 g [11], the liquid limit is 135 ± 5% and the plastic limit 48 ± 5% [11,12]. Further details on the geochemical and geotechnical parameters can be found in [11] and [13].…”
Section: Bcv Bentonitementioning
confidence: 99%
“…The laboratory experiments were simulated by means of a thermo-hydro-mechanical hypoplastic model for bentonite [14,15] implemented in the SIFEL coupled finite element code [16]. The calibration and validation of the model using data obtained from BCV bentonite laboratory (single-density) samples, details of which are available elsewhere [13], proved its high level of performance with respect to experiments of various types when modelled using a single parameter set. The experiments used for calibration purposes included the testing of swelling pressure and oedometric swelling under constant loading at differing initial dry densities, the oedometric loading and unloading testing of saturated samples, water retention tests under confined and free swelling conditions at various initial dry densities and the uniaxial compression testing of unsaturated samples.…”
Section: Numerical Simulationsmentioning
confidence: 99%